Quantifying the risk of disease reactivation after interferon and glatiramer acetate discontinuation in multiple sclerosis: The VIAADISC score. (18th January 2021) - Bsteh, Gabriel; Hegen, Harald; Riedl, Katharina; Altmann, Patrick; Auer, Michael; Berek, Klaus; Di Pauli, Franziska; Ehling, Rainer; Kornek, Barbara; Monschein, Tobias; Rinner, Walter; Schmied, Christiane; et al.
Abstract: Background and purpose: There is a lack of evidence guiding discontinuation of disease‐modifying therapy (DMT) in relapsing multiple sclerosis (RMS). Thus, the objective of this study was to generate and validate a risk score for disease reactivation after DMT discontinuation in RMS. Methods: We drew a generation and validation dataset from two separate prospectively collected observational databases including RMS patients who received interferon‐β or glatiramer acetate for ≥12 months, then discontinued DMT for ≥6 months and had ≥2 years of follow‐up available. In the generation sample ( n  = 168), regression analysis was performed to identify clinical or magnetic resonance imaging (MRI) variables independently predicting disease reactivation after DMT discontinuation. A predictive score was calculated using the variables included in the multivariable model and applied to the validation sample ( n  = 98). Results: The variables included in the final model as independent predictors of disease reactivation were age at discontinuation, MRI activity at discontinuation, and duration of clinical stability (all p  < 0.001). The resulting score was able to robustly identify patients at high (83%–85%), moderate (36%–38%), and low risk (7%) of disease reactivation within 5 years after DMT discontinuation in both cohorts. Conclusions: The composite VIAADISC score is a valuable tool to inform and support patients and neurologists in the process of decision making to discontinue injectable DMTs. Abstract : The objective of this study was to generate and validate a risk score for disease reactivation after disease‐modifying therapy (DMT) discontinuation in relapsing multiple sclerosis. From two separate prospectively collected cohorts, a predictive score including three independent predictors of disease reactivation (age at discontinuation, magnetic resonance imaging activity at discontinuation, and duration of clinical stability) was generated. The resulting score was able to robustly identify patients at high (83%–84%), moderate (35%–38%), and low risk (7%) of disease reactivation within 5 years after DMT discontinuation.